Perspective Legal Theory Analysis Mixed Marriage Arrangements As An Instrument Of Prevention Legal Smuggling In Business Development - Herlina, Putu; Bagus Wyasa Putra, Ida; Wayan Windia, I; Putu Dewi Kasih, Desak (International Journal of Educational Research & Social Sciences, 2023)
Various cases of mixed marriages show that not all mixed marriages are based on the motive of forming a happy family and continuing offspring, but there are also mixed marriages with other motives, including business, by using the Indonesian citizen partner as a tool to control land. property rights status and carrying out business activities at lower costs. According to the Basic Agrarian Law in Indonesia, foreign nationals are prohibited from controlling land with ownership status. The Basic Agrarian Law in Indonesia prohibits Indonesian citizens from controlling land with ownership status and only allows foreigners to hold land rights on Right to Use or Right to Use Building if they have formed a Limited Liability Company. The research method used in this research is the normative juridical research method. The research results show the importance of a legal theoretical basis in establishing mixed marriage arrangements as an instrument for preventing legal smuggling in business development in Indonesia. and proportionally placing marriage and business as different legal events, in accordance with statutory regulations, as well as returning mixed marriages to their natural, social and cultural aims and objectives, so that Indonesian citizen couples in mixed marriages can enjoy their constitutional rights as partners in a marriage like marriage in general.